Balance Hídrico y Calculo de Eficiencia de Riego del Reservorio Garrapón – Valle Chicama, para evaluación de áreas de influencia - Paredes Aguilar, Diego Arturo (2017)
The work presented was carried out at the Casa Grande Company in the area of the Garrapon reservoir, with the information of volumes consumed during the period 2013-2016. This work analyzes and calculates the water balance presented by the reservoir, and then evaluates the efficiency and efficient management of the water resource stored in the reservoir for the irrigation of fields under its influence, to adequately and timely satisfy the water requirements that the cultivated sugar cane needs. The Casa Grande Company controls only the in and out of the waters of the Garrapon Reservoir, but doesn’t take into account additional parameters such as evaporation and precipitation, which must be considered in the total balance sheet. The values obtained from the water balance of the Garrapon Reservoir are determining values for an adequate irrigation program in the future. For the water balance it were also used, data recorded in the meteorological station Casa Grande, station belonging to Casa Grande, approved and authorized by SENAMHI. At present, Casa Grande has different sources of irrigation supply, in addition to the main ones that are: river water and tubular wells, these are: factory and population effluents wich are used by been treated first. The water balance of the Garrapon Reservoir is positive, measurements made in the period 2013-2016 give an annual surplus of 3,500,000.00 m3 greater than the minimum technical reserve of the order of 300,000.00 m3. This surplus of 3.5 million cubic meters per year would serve to include irrigation of 152 hectares of sugar cane, under the modality of irrigation by gravity practiced in the company. The efficiency of the Garrapon Reservoir measured in the period 2013-2016 is 43% average over the period analyzed. The water supply per month of the Garrapon Reservoir is 718,022.78 in 2013, 651,403.20 in 2014, 382,738.47 in 2015 and 449,430.11 in 2016.